The Thoracic Lordosis Correction Improves Sacral Slope and Walking Ability in Neuromuscular Scoliosis. Issue 8 (October 2016) - Kim, Do Yeon; Moon, Eun Su; Park, Jin Oh; Chong, Hyon Su; Lee, Hwan Mo; Moon, Seong Hwan; Kim, Sung Hoon; Kim, Hak Sun
Abstract : Study Design: Retrospective study. Objective: To report on neuromuscular patients with preserved walking ability, but forward bending of the body due to thoracic lordosis, and to suggest thoracic lordosis correction as the surgical treatment. Summary of Background Data: It is an established fact that lumbar lordosis or pelvic parameter is directly related to thoracic sagittal balance. However, the reverse relationship has not been fully defined yet. Loss of thoracic kyphosis results in positive sagittal balance, which causes walking difficulty. Neuromuscular patients with thoracic lordosis have not been reported yet, and there have been no reports on their surgical treatments. Methods: This study analyzed 8 patients treated with thoracic lordosis correction surgery. Every patient was diagnosed with muscular dystrophy. In thoracic lordosis correction surgery, anterior release was performed in the first stage and posterior segmental instrumentation was performed in the second stage. Radiographic parameters were compared and walking ability was evaluated with gait analysis. All patients were classified according to the modified Rancho Los Amigos Hospital system preoperatively and 2 years postoperatively to evaluate functional ability. The average follow-up period was 2.9 years. Results: Before surgery, the mean thoracic sagittal alignment was −2.1-degree lordosis, the mean Cobb angle and sacral slope increased to 36.3 and 56.6 degrees, respectively. The anterior pelvic tilt in gait analysis was 29.3 degrees. At last follow-up after surgery, the mean thoracic sagittal alignment changed to 12.6-degree kyphosis, and the Cobb angle and sacral slope decreased to 18.9 and 39.5 degrees, respectively. Lumbar lordosis and the sacral slope showed significant positive correlation ( P <0.001). The improvement in thoracic lordosis showed a significant correlation to the preoperative flexibility of the major curve ( P =0.028). The anterior pelvic tilt in gait analysis improved to 15.4 degrees. The functional ability improved in 2 (50%) of 4 patients in class 2 and maintained in remaining 6 patients 2 years after surgery. Conclusions: Thoracic lordosis correction surgery in neuromuscular scoliosis patients with thoracic lordosis improved the sacral slope in the standing position and the anterior pelvic tilt in gait. Sagittal imbalance was compensated by the spinopelvic mechanism, and back and hip extensor muscles seem to play a major role in this compensation.